Le patrimoine du cheval paysan. Musées de l’agriculture et de la vie rurale en France : statuts, collections, la place du cheval - Georges Carantino (In Situ)
The farmer’s horse and its heritage, museums of agriculture and rural life in France. Museums of agriculture and rural life preserve the memory of the French past where agriculture and country life are concerned. The specific heritage relating to the horses used on the land are an important feature in these museums: equipment for horse breeding and care, tacks, horse-drawn vehicles (carts, large four-wheeled wagons, tumbrels…). The work of blacksmiths, wheelwrights and harness and saddle makers is often presented. Photographs, drawings, archival resources and technical publications provide information about the objects on display. It is a heritage which is sometimes threatened, but also a living heritage. Animations and rides attract large numbers of visitors.